Effect of additional uphill treadmill exercise combined with standard therapy on walking speed in patients with knee osteoarthritis - Taurisia Kristiani; Damayanti Tinduh; Dyah Intaniasari; Soenarnatalina (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Knee osteoarthritis (OA) is a progressive musculoskeletal condition that limits mobility by reducing walking speed. Exercise therapy can improve walking speed in knee OA patients. This research aimed to demonstrate that the addition of uphill treadmill exercises to standard therapy protocols was more effective in enhancing walking speed in patients with grade II and III knee osteoarthritis compared to standard therapy alone. Methods: This randomized controlled trial at Dr. Soetomo General Hospital included 36 patients with knee OA grade II-III (Kellgren-Lawrence scale), aged 50-60 years, BMI <30 kg/m², moderate pain (VAS 30-60mm), and independent walking ability. Exclusion criteria included recent knee injuries/surgeries, intra-articular injections, acute inflammation, inflammatory arthritis, significant deformities, uncontrolled cardiovascular/diabetes conditions, respiratory disorders, sensory disturbances, balance disorders, concurrent therapy, pacemaker contraindications, cognitive impairment, and substance abuse. Subjects were randomized into control (n=18) and treatment groups (n=18). Controls received standard therapy (Q-bench strengthening and TENS). The treatment group received identical standard therapy plus uphill treadmill exercise (8-degree inclination, 1.1 m/s, 30 minutes) twice weekly for 5 weeks. Walking speed was assessed using 10-Meter Walk Test at baseline, post-intervention, and 20-day follow-up. Results: The treatment group demonstrated significantly superior walking speed improvements compared to controls. No baseline differences existed (p-value= 0.680; Cohen's d= 0.14), but significant improvements occurred at post-intervention (p-value= 0.030; Cohen's d= 0.79) and 20-day follow-up (p-value =0.02; Cohen's d= 0.83). Conclusion: There was a significant improvement in walking speed in post-exercise measurements and follow-up measurements in grade II-III knee OA patients who received additional uphill treadmill training compared to standard exercises.